Innovative solutions for low power photovoltaic water pumping systems - development of a DC-DC step-up converter - Fey, Alice Nogueira (2020)
It is known that the use of Photovoltaic Water Pumping Systems (PVWPS) is a solution to supply water to populations living in arid and remote regions. But there are still problems regarding costs and market availability of PVWPS. These systems are usually sold as closed kits and with solar energy dedicated equipment. This situation makes it difficult to replace damaged equipment for other that would be available on the market. Also, solar dedicated equipment are more expensive than the general-purpose ones. Another issue is the oversizing of the PV panel in terms of power, when installing low power PVWPS that employ conventional AC motor-pumps. The oversizing occurs in order to achieve the voltage requirements of these water pumps. With the aim of solving the problems mentioned above, this work proposes four innovative solutions for low power PVWPS. The proposed solutions are for installations up to 750W (1HP); employ a maximum of 4 photovoltaic modules; are composed of standard frequency converters and AC motor-pumps. Also, a simple and cost-effective DC-DC voltage step-up converter was conceived to be a part of the suggested PVWPS. It was designed and tested a 750W DC-DC step-up converter with a static gain of 3.44. One of the proposed solutions for low power PVWPS employing the designed DC-DC step-up converter was tested in a laboratory environment and successfully validated. The system was tested under distinct weather conditions and showed promising results. It was verified that is possible to conceive a PVWPS based on standard frequency converters and other conventional components. The present work was made in cooperation with the company VALLED. The goal was to work together with the company in order to develop a modular, reliable, robust and cost effective solution.